2022
DOI: 10.1111/mcn.13407
|View full text |Cite
|
Sign up to set email alerts
|

Views and experience of breastfeeding in public: A qualitative systematic review

Abstract: Breastfeeding rates in many Global North countries are low. Qualitative research highlights that breastfeeding in public is a particular challenge, despite mothers often having the legal right to do so. To identify barriers and facilitators, we systematically searched the qualitative research from Organisation for Economic Co‐operation and Development countries relating to breastfeeding in public spaces from 2007 to 2021. Data were analysed using the Thematic Synthesis technique. The review was registered with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 89 publications
0
20
0
2
Order By: Relevance
“…In this case, the discomfort caused by breastfeeding does not stem from the child's age, but from the idea that breastfeeding should be done in private, with modesty, because it is something that breaks the rules of social interaction, largely due to the sexual connotation of the woman's breasts. In every paper of their systematic literature review, Grant et al ( 2022 ) identified discourses suggesting that breastfeeding was viewed as an antisocial act to be conducted in private only. Such discourses were largely related to the sexualization of breasts.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the discomfort caused by breastfeeding does not stem from the child's age, but from the idea that breastfeeding should be done in private, with modesty, because it is something that breaks the rules of social interaction, largely due to the sexual connotation of the woman's breasts. In every paper of their systematic literature review, Grant et al ( 2022 ) identified discourses suggesting that breastfeeding was viewed as an antisocial act to be conducted in private only. Such discourses were largely related to the sexualization of breasts.…”
Section: Resultsmentioning
confidence: 99%
“…Although support is available for breastfeeding mothers, low-income Black women have reported lack of social, workplace, and cultural support as barriers to breastfeeding 3,29. These barriers may be exacerbated by a lack of cultural acceptance of breastfeeding, especially in public 29,33…”
Section: Health Inequitiesmentioning
confidence: 99%
“…The need to increase rates of breastfeeding among Black women is especially relevant considering the recent baby formula shortage. However, there is a need for cultural change to reduce the stigma associated with breastfeeding 33. The role of educating the public in this capacity cannot be overstated.…”
Section: Health Inequitiesmentioning
confidence: 99%
See 2 more Smart Citations